Calidad del servicio logístico de Serpost para las mypes de comercio electrónico internacional del sector joyería de Lima - Ramirez Huamani, Abdel Andre Layonel (2020)
Exporting is one of the internationalization strategies that companies can apply to start their development in the international business. Precisely, micro and small companies in Peru have the "Exporta Fácil" program, which offers through Serpost (Peruvian Postal Service), a unique logistics service to export easily and economically. However, according to the 2018 Logistics Performance Index published by the World Bank, Peru is below the Latin American average. And regarding the "Exporta Fácil" service, the Association of Exporters (Adex) identified several weaknesses in a survey conducted in 2014, a situation that could continue today. In this regard, an investigation was undertaken focused on the sector that has the greatest representation among the users of “Exporta Fácil”, which are the micro and small jewelry companies and recognizing that they use international electronic commerce as a sales channel. Given the importance of these micro and small companies accessing a quality logistics service, the research aims to measure the level of quality of Serpost's logistics service for micro and small jewelry companies of Lima that sell through international electronic commerce and generate recommendations for improving the service. To achieve this, the Servqual method was applied, which implies obtaining data on the expectations and perceptions of the sector under study to calculate the Servqual ratings for each dimension of the method and an overall rating of the quality of the service. From the processing and interpretation of the data, it was found that the quality of Serpost's logistics service for micro and small jewelry companies of Lima that sell through international ecommerce presents gaps in all the dimensions analyzed. Given this, recommendations were formulated focused on the 10 items of the Servqual method that presented the greatest deficiency.